2011
DOI: 10.4172/jbb.1000097
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pharmacokinetic Studies in Drug Discovery

Abstract: Over the last few years, Pharmacokinetics has emerged as an integral part of drug development, especially when identifying a drug's biological properties. Understanding of pharmacokinetic and metabolism characteristic of the drug compounds is needed in designing appropriate human clinical trials. This document describes the basic principles of pharmacokinetic studies necessary for the submission of a new drug application and for re-examination of approved drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Absorption features outlined that HSP is moderately soluble in water (QPlogPo/w ¼ 1.803), moderate Caco-2 permeable, 75.45% absorbed human orally, act as a P-glycoprotein substrate, and have good skin penetrability (QPlogKp ¼ -4.071). Distribution refers to drug movement within the body and depends on several factors i,e, BBB permeability, CNS permeability, binding to plasma protein, and many more [141]. Our predicted result suggested that HSP has the potentiality to cross the blood-brain barrier (QPlogBB ¼ -1.512), penetrate to CNS (CNS ¼ -2), and have a high affinity to bind with Human serum albumin (QPlogKhsa ¼ 0.018).…”
Section: Pharmacokinetics and Future Perspective In Drug Developmentmentioning
confidence: 93%
See 2 more Smart Citations
“…Absorption features outlined that HSP is moderately soluble in water (QPlogPo/w ¼ 1.803), moderate Caco-2 permeable, 75.45% absorbed human orally, act as a P-glycoprotein substrate, and have good skin penetrability (QPlogKp ¼ -4.071). Distribution refers to drug movement within the body and depends on several factors i,e, BBB permeability, CNS permeability, binding to plasma protein, and many more [141]. Our predicted result suggested that HSP has the potentiality to cross the blood-brain barrier (QPlogBB ¼ -1.512), penetrate to CNS (CNS ¼ -2), and have a high affinity to bind with Human serum albumin (QPlogKhsa ¼ 0.018).…”
Section: Pharmacokinetics and Future Perspective In Drug Developmentmentioning
confidence: 93%
“…Pharmacokinetic studies help determine the effects of respective drugs in the body based on absorption, distribution, metabolism, excretion, and toxicity. These pharmacokinetic properties are called ADMET [141]. Analysis of these properties aid in designing a drug to treat numerous diseases in medical society with understanding potential risk, time, and cost to determine whether or not a compound is suitable to proceed to the clinical stage.…”
Section: Pharmacokinetics and Future Perspective In Drug Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…After absorption, consequentially comes distribution, another principal descriptor for drug development, which depends mumerous factors i.e., steady-state volume of distribution (VDss), blood-brain barrier (BBB) and central nervous system(CNS) permeability, binding to plasma protein, and many more [117].Our analysis suggested that Gen has the potentiality to have a poor…”
Section: Clinical Trialsmentioning
confidence: 94%
“…Due to the emergence and spread of multidrug-resistant bacteria, the development of new drugs for use in animals and humans has become increasingly necessary. In this context, pharmacokinetic studies are an important and indispensable step of drug development [ 2 ].…”
Section: Introductionmentioning
confidence: 99%